ANALYSIS OF THE INFLUENCE OF ATTITUDE AND BEHAVIORAL CONTROL ON THE FINANCIAL PERFORMANCE OF MSMES IN NUSANIWE DISTRICT - Rita J D Atawarman; Theovilia L Bernadus; Rifki Kurniawan; Arleston Pelupessy (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, yet they still face the challenge of suboptimal financial performance. This study aims to analyze the direct influence of Financial Attitudes and Behavioral Control on MSME Financial Performance and examine the mediating role of Financial Behavior in this relationship. This study is grounded in the Theory of Planned Behavior (TPB), which positions attitudes and behavioral control as the primary determinants of individual intentions and behavior. Using a quantitative approach, this study will test hypotheses on 31 MSME owners/managers in Nusaniwe District, selected through purposive sampling. Data will be collected through a Likert-scale questionnaire and analyzed using SPSS statistical software. Validity, reliability, and multiple regression tests will test the simultaneous influence of attitudes, control, and behavior on financial performance. The results are expected to provide insight into the importance of behavioral aspects (attitudes and control) in improving MSME financial performance and contribute to more effective mentoring programs and policy formulation